Cross sections of some efficient slow-neutron reflectors - Dr Javier Dawidowski; Dr Granada; Dr Goran Skoro; Dr Giovanni Romanelli; Dr Luis Rodríguez Palomino; Dr Jose Ignacio Marquez Damian (ISIS Facility, 2019)
The proposal seeks to investigate the reflection capacity of two systems that are candidates for use in the design of cold neutron sources. These are carbon nanodiamonds and magnesium hydride. The first shows a strong Small Angle Neutron Scattering component in its cross section, while the second has scattering distributions closer to the isotropy. The comparison between forward and backward scattering signals will serve to evaluate such properties. In addition, the transmission measured with the new 2D transmission detector will serve to confirm the presence of the SANS signal in the nanodiamond powder in contrast to the magnesium hydride. The DINS spectra will be used to analyze the effective temperatures of the atoms, a quantity that will be used in the formulation of the dynamic models of both systems, necessary to model the materials to perform Monte Carlo simulations.
Keywords: STFC ISIS Neutron and Muon Data